HUBUNGAN KELENTURAN OTOT PUNGGUNG DAN EKSPLOSIVE POWER OTOT TUNGKAI DENGAN KETERMPILAN HEADING DALAM PERMAINAN SEPAK BOLA PADA TIM SEPAK BOLA EKSTRAKURIKULER SMAN 1 SABAK AUH - Triono '; ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is less stud ents ekstrakulikuler soccer when doing heading. There are still many students who have not been able to control the ball in the air properly, it is seen when students do duel in the air, especially when heading a lot of non-directional ball that should be able to take advantage of heading to control the ball in the air to pocket the ball to a friend, and To score goals. This study aims to determine whether there is a correlation between back muscles and explosive muscle limb muscles with heading skill in the game of soccer on extracurricular soccer team SMAN 1 Sabak Auh. Sampling technique that is the total population (total sampling) extracurricular football team SMAN 1 auh berjumblah 17 people. This research uses correlation technique. Then, the test data using normality test, product test moment correlation, and test that L calculate variable X1 = 0.2011, L calculate variable X2 = 02005 and L calculate variable Y = 0.1330 where L table obtained 02060 (α = 0,05), with So L calculate = 0.2011 <L table 0.2060 on variable X1, L count 02005 <L table = 0.2060 on the variable X2 and L arithmetic = 0.1330 <L table = 0.2060 on variable Y, in other words it is concluded that X1, X2 and Y data are distributed normal.Keywords: Back Muscle Flexibility, Explosive Power Muscle Foot Heading Skill